Pengaruh Pengembangan Karier dan Kompensasi terhadap Turnover Intention pada Karyawan Pt X Merak-Cilegon - Nana Sutisna; Muhammad Suparmoko; Ende Ende (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine the effect of career development and compensation on employee turnover intention at PT X Merak–Cilegon. The phenomenon of high turnover intention among employees at the Operator/Clerk/Technician to Supervisor levels has highlighted the need to investigate the factors influencing employees' intentions to leave the company. Career development and compensation were selected as the independent variables because the results of the preliminary survey indicated that these factors were the most dominant determinants affecting turnover intention This study employed a quantitative research method with a survey approach. The population consisted of employees of PT X at the Operator/Clerk/Technician to Supervisor levels. The sampling technique used was proportional random sampling, resulting in a sample of 170 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results of the study indicate that career development has a negative and significant effect on turnover intention. Compensation also has a negative and significant effect on turnover intention. Simultaneously, career development and compensation have a significant effect on employee turnover intention. These findings suggest that the better the career development opportunities provided by the company and the fairer and more adequate the compensation received by employees, the lower the level of employee turnover intention.